Manufacture of Immunoglobulin Products for Patients with Primary Antibody Deficiencies – The Effect of Processing Conditions on Product Safety and Efficacy - Farrugia, Albert; Quinti, Isabella (Frontiers in Immunology, 2014)
Early preparations of immunoglobulin (Ig) manufactured from human plasma by ethanol (Cohn) fractionation were limited in their usefulness for substitution therapy in patients with primary antibody deficiencies (PAD), as Ig aggregates formed during manufacture resulted in severe systemic reactions in patients when given intravenously. Developments in manufacturing technology obviated this problem through the capacity to produce concentrated solutions of intact monomeric Ig, revolutionizing PAD treatment and improving patient life expectancy and quality of life. As the need for Ig has grown, manufacturers have refined further manufacturing technologies to improve yield from plasma and produce therapies, which are easier and less expensive to deliver. This has led to the substitution, partly or wholly, of ethanol precipitation by other techniques such as chromatography, and has also stimulated the production of highly concentrated solutions capable of rapid infusion. Ig products have been associated, since their inception, with certain adverse events, including infectious disease transmission, hemolysis, and thromboembolism. The introduction of standardized manufacturing processes and dedicated pathogen elimination steps has removed the risk of infectious disease, and the focus of attention has shifted to other problems, which appear to have increased over the past 5 years. These include hemolysis and thromboembolism, both the cause for substantial concern and the subject of recent regulatory scrutiny and actions. We review the development of manufacturing technology and the emerging evidence that changes for the optimization of yield and convenience has contributed to the recent incidents in certain adverse events. Industry measures under development will be discussed in terms of their potential to improve safety and optimize care for patients with PAD.